O DESAFIO DE UMA PRÁTICA EDUCATIVA HUMANIZADA: A EXPERIÊNCIA COM AS CARTAS PEDAGÓGICAS - Ferreira, Jose Luiz (Revista Didática Sistêmica, 2026)
The text in the format of a Pedagogical Letter aims to communicate ideas and reflections on the use of Pedagogical Letters from the perspective of building and developing humanized educational practices in higher education. It is based on an experience in the Pedagogy Course at a public university, focusing on learning assessments in the course's curriculum components. The theoretical-methodological inspiration is Freirean, for which the pedagogical letter represented a political-pedagogical-ethical-aesthetic strategy. The text contains two main points: the assumptions of a humanized educational practice and the experience with Pedagogical Letters. Through the letter, the hope is to continue the dialogue and to foster that the production of knowledge in higher education does not distance, but rather brings closer, the people involved.